2009
DOI: 10.1111/j.1540-8167.2009.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrode Orientation on Lesion Sizes Produced by Irrigated Radiofrequency Ablation Catheters

Abstract: Effect of Electrode Orientation on Lesion Sizes. Background: Irrigated radiofrequency (RF)ablation catheters may produce different lesion sizes dependent upon the electrode orientation to the tissue. This study examined the effect of irrigated electrode orientation on the lesion size and explores a potential mechanism for this effect.Methods and Results: Lesions were created in isolated porcine myocardium using an open irrigation, closed irrigation, and nonirrigated RF catheter (all 3.5-4 mm tips). Lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 16 publications
2
51
0
Order By: Relevance
“…Since Method 4 provides the most realistic modeling approach, this was considered as the reference method, and the results from the other three methods were compared to it. We considered that the differences in lesion depth and width were insignificant for values lower than 1 mm, since this value is approximately that of the deviation (±0.5 mm) observed in experimental RFCA studies with a non-irrigated electrode [22,36]. Likewise, the differences in T max_tissue or T max_blood were considered to be insignificant for values lower than 4ºC, since this value is approximately that of the observed deviation (±2ºC) [22].…”
Section: F Assessment Of the Thermal Lesion Dimensions And Comparisomentioning
confidence: 99%
“…Since Method 4 provides the most realistic modeling approach, this was considered as the reference method, and the results from the other three methods were compared to it. We considered that the differences in lesion depth and width were insignificant for values lower than 1 mm, since this value is approximately that of the deviation (±0.5 mm) observed in experimental RFCA studies with a non-irrigated electrode [22,36]. Likewise, the differences in T max_tissue or T max_blood were considered to be insignificant for values lower than 4ºC, since this value is approximately that of the observed deviation (±2ºC) [22].…”
Section: F Assessment Of the Thermal Lesion Dimensions And Comparisomentioning
confidence: 99%
“…Lesions characteristics, if RF had been applied at different sites, may have been different because of differing loads on the catheter dependent on the angle at which the catheter tip makes contact with the tissue. 8 Other variables such as electrode surface area in contact with the tissue and local blood flow known to effect lesion formation could not be controlled. Prevalence of ventricular arrhythmias during RF application is much higher in animal model compared with patients.…”
Section: Limitationsmentioning
confidence: 99%
“…The electrode orientation has previously been shown to influence lesion characteristics in a bench model. 8 In atrium, optimal CF has been evaluated around 20 g. 6,[9][10][11] Concerning safety, minimal forces to perforate ventricles mechanically (without RF delivery) are higher than for atria ; however, the force required to perforate when RF is delivered can be as low as 77 g in the atrium. 13 Whereas it has been shown that CF was correlated with lesion volume, 6 it seems that a parameter coupling instantaneous total force and application duration (FTI) 4 was more accurate to predict lesion size.…”
Section: Lesion Formationmentioning
confidence: 99%
“…This is in contrast to contact irrigated catheter ablation, in which energy delivery may vary significantly depending on catheter orientation as a result of the variable electrode/myocardial interface and loss of energy to the surrounding blood pool. 22 Finally, the flat 6-mm distal hood surface is also less likely to lead to cardiac perforation; we have never seen a perforation despite aggressive catheter manipulation in this animal model.…”
mentioning
confidence: 95%